Māori Sovereignty or Death - Rata, Arama; Brayne, Gabriella; Barber, Simon (Decolonization of Criminology and Justice, 2023)
In her 1984 book ‘Māori Sovereignty’, Donna Awatere sustains a blistering polemic on ‘white culture’ that still retains its rhetorical force 40 years later. Her construction of a sharply delineated binary between a monolithic notion of ‘white culture’ as against ‘taha Māori’ can come at the cost of simplification. But this is not at all to say that Awatere is wrong when she says it is ‘Māori Sovereignty or death’. In this paper, we extend Awatere’s work by analysing relationships between colonialism and capital. We begin by situating Awatere’s work in its historical context, outlining major shifts in the global political economy, and drawing on Awatere’s analysis of Fascism to account for contemporary Far Right movements. Building from the inextricability of Fascism from the settler colonial/imperialist economy, we explore Awatere’s framing of whiteness as a system of racial exploitation and violence that enforces the state’s genocidal claims to sovereignty, defined through necropower – capitalism’s consumption of racialised death. We then consider the contradictions between capitalism and constitutional transformation. By scanning revolutionary movements elsewhere (in particular the Chilean movement for plurinationalism), we identify the need for extra-parliamentary, broad-based, popular power and constituent authority from below, as well as Indigenous solidarities and international alliances to circumvent anti-Māori populism and confront capital. In reflecting on the power of death, and the need for counter-hegemonic culture capable of securing the transition out of capitalism, we are drawn to the revolutionary essence of whakapapa as an Indigenous ontology that eternally resists necropower.

Settler/Invader Identity and Belonging in Aotearoa New Zealand: Critiquing “Tāngata Tiriti” and Moving Toward the Collective Future - Simon, Hemopereki (Ethnic Studies Review, 2023)
This Kaupapa Māori writing inquiry explores “Tāngata Tiriti” (People of the Treaty) as a settler/invader identity term in Aotearoa New Zealand. Derived from the failed policy platform of “biculturalism” and “Indigenous inclusion,” Tāngata Tiriti is a byproduct of neoliberalism and settler/invader colonialism that fails to provide for Indigenous inclusion, mana motuhake (Indigenous sovereignty) and tino rangatiratanga (self-determination). This article argues that Tāngata Tiriti should be abandoned due to the 2014 paradigm shift surrounding Te Tiriti o Waitangi (Te Tiriti) and mana motuhake from the Te Paparahi o Te Raki report and the author’s subsequent research on non-signatory hapū and iwi. Pākehā settler/invader perspectives on Tāngata Tiriti are compared with Tāngata Moana and Asian scholarly understandings. The author advocates adopting Tāngata Moana thinking around letting Māori as mana whenua lead “wayfinding” and “meaning-making” to define allyship and promote a “collective future” together based on Māori constitutional values that are generally universal throughout Pacific cultures. Instead of settler/invader identity constructs and the doctrine of the nation as a White possession, movement toward a collective future must begin from a place of sovereign relationality. The pedagogy of teaching Te Tiriti must change, the ill-conceived Tāngata Tiriti identity must be abandoned, and “New Zealand” as a settler/invader colonial enterprise must end. Our future must be post-settler/invader colonial and post-Tiriti and must recognize unceded mana motuhake or sovereignty.

Māori Issues - Mutu, Margaret (The Contemporary Pacific, 2023)

New Zealand's ‘Maori foreign policy’ and China: a case of instrumental relationality? - Smith, Nicholas Ross; Holster, Bonnie (International Affairs, 2023)
In 2021, Aotearoa New Zealand's Foreign Minister, Nanaia Mahuta, sketched out a kaupapa Māori (collective Māori vision) foreign policy for New Zealand based on four tikanga Māori (Māori customary practices and behaviours): manaakitanga (hospitality), whanaungatanga (connectedness), mahi tahi and kotahitanga (unity through collaboration), and kaitiakitanga (guardianship and the protection of intergenerational wellbeing). This article makes a novel contribution to the global International Relations body of literature by questioning to what extent New Zealand's ‘Māori foreign policy’ has been applied to its relationship with China. Through assessing the communications of Mahuta and other officials, it is found that New Zealand is utilizing a kaupapa Māori framework towards China: ‘the taniwha and the dragon’. It is argued that New Zealand is attempting to consolidate the maturity of the Sino-New Zealand relationship, as well as differentiate itself from the other Anglosphere countries that have recently pushed back on China. In doing so, not only is New Zealand something of an outlier, it is demonstrating how eschewing a western-centric understanding of foreign policy for a more relational view based on indigenous knowledge and perspectives (in this case, from te ao Māori: the Māori worldview) can be applied at a time of increasing great power competition.

Critical Tiriti Analysis: A prospective policy making tool from Aotearoa New Zealand - O’Sullivan, Dominic; Came, Heather; Kidd, Jacquie; McCreanor, Tim (Ethnicities, 2023)
Restrictions on Indigenous peoples’ contributions to policymaking pervade post-settler societies like Australia, Canada and Aotearoa. Such effects are observed in spite of agreements like Te Tiriti o Waitangi in Aotearoa and the United Nations’ Declaration on the Rights of Indigenous Peoples. Te Tiriti, negotiated between the British Crown and Māori (Indigenous peoples of Aotearoa), may have been entered into honourably by both parties, but the Crown has consistently resisted its implementation. Contemporary colonialism is characterised by the entrenched and on-going displacement of Indigenous people’s authority by settler states, rationalised by race as a determinant of human worth. Impacts include land alienation, unsustainable resource exploitation and marginalising Indigenous voices from opportunities to make policy consistent with Indigenous values and preferred ways of living. Colonialism normalises institutional racism so that public policy outcomes are persistently unjust. This article describes Critical Tiriti Analysis (CTA), an original contribution to transforming colonial policy, which retrospectively evaluates whether any specific policy document is consistent with Te Tiriti. Substantial interest in CTA from policymakers, practitioners, and scholars led to the development of the tool as a prospective guide to making policy that is consistent with authoritative interpretations of Te Tiriti, and therefore, more likely effective in producing public policies which eliminate inequities. CTA was initially focused on health policy and built on a series of questions that arise from our interpretations of the text of Te Tiriti, contemporary Tiriti scholarship and jurisprudence, and our observations of the ways in which the method is being used by ourselves and others. Although deeply grounded in Aotearoa, we argue that CTA may be transferable to other colonial contexts, such as the Australian where treaties between First Nations and the state are being contemplated, and Canada which has passed legislation to implement the Declaration on the Rights of Indigenous Peoples.
Keywords: Public Policy; Te Tiriti o Waitangi

Co-Governance and the Case for Shared Decision Making - Jones, Carwyn (Policy Quarterly, 2023)
This article explores some of the key features of co-governance, or shared decision making, between Māori and the Crown. Co-governance models create the conditions for making better decisions by sharing decision making with Māori where Māori communities have a distinctive interest. Such models are able to draw on the distinctive experiences, knowledge and expertise that Māori communities can bring. Shared decision making enhances the legitimacy and durability of decisions by giving effect to rights under te Tiriti o Waitangi. The article also identifies some key principles of effective co-governance and provides some brief examples where shared decision making is being implemented to illustrate the range of situations in which such models are applicable.
Keywords: Co-Governance; Treaty settlements

Moving beyond “Contingent”: Descriptive Representation by and for Indigenous Peoples - Greaves, Lara; Curtin, Jennifer (Politics & Gender, 2023)
When Jane Mansbridge’s (1999) article was first submitted, more than 80% of the world’s parliaments featured less than 20% women (IPU 2015). Calculating the parliamentary presence of ethnic and cultural minorities and Indigenous peoples has proved more difficult (Protsyk 2010). This is despite the adoption of two United Nations Declarations, on the Rights of Persons Belonging to National or Ethnic, Religious and Linguistic Minorities (1992) and on the Rights of Indigenous Peoples in 2007. In Aotearoa New Zealand, the representation of women and Māori (the Indigenous peoples) was comparatively better than global averages. In 1996, 29% of parliamentarians were women and 14% were Māori. By 2020, these figures had increased to 48% and 21%, respectively, while in the cabinet, women made up 40% of ministers and Māori accounted for 25%. Reported as the country’s historically most diverse parliament and cabinet (Curtin 2020), it appears that both new (proportional representation) and old (reserved seats for Māori) institutional mechanisms had achieved near proportionality, and a heterogeneity of experiences, potentially enhancing opportunities for deliberation.
Keywords: Identity; Representation; Voting, Parties, Parliament

Māori Linked Administrative Data: Te Hao Nui - A novel Indigenous Data Infrastructure and Longitudinal Study - Boulton, Amohia; Theodore, Reremoana; Sporle, Andrew (The International Indigenous Policy Journal, 2023)
Worldwide, large amounts of administrative data are collected within official statistics systems on Indigenous Peoples. These data are primarily used for government and state policy purposes as opposed to by Indigenous Peoples to support Indigenous agendas (Taylor & Kukutai, 2017). In Aotearoa me Te Waipounamu New Zealand, Māori need high quality data to develop evidence-based policies and programs and to monitor government policies that impact on Māori. In this methodological paper, we describe uses of administrative data for Māori and current barriers to its use. We outline the development of a novel administrative data infrastructure and future longitudinal study. By explicating our Indigenous initiated, designed and controlled data project, we make a methodological contribution to Indigenous Data Sovereignty and Kaupapa Māori (Māori worldview) epidemiology.
Keywords: Indigenous data sovereignty; Māori; administrative data; policy; wellbeing; youth

Towards a fairer and more tika political science and politics: Are political science programs equipping students adequately for Aotearoa realities? - Te One, Annie; Bargh, Maria (Australian Journal of Indigenous Education (Online), 2023)
Social and political change is occurring in Aotearoa New Zealand and tikanga, matauranga, te reo Maori (the Maori language) and Te Tiriti o Waitangi (Treaty of Waitangi) are increasingly being recognised in diverse political and legal contexts. This article explores whether the political science discipline in Aotearoa New Zealand is keeping pace with these political changes, whether research and course content is adequately reflecting these new realities, and if students are appropriately equipped to participate. In particular, we examine the state of university politics programs and outline the form and quantity of Maori politics in the teaching and research of these programs. From the assessment of the current state of politics programs, we make some observations about what changes may be required to ensure politics programs, their students and academics are fully equipped to work in the unique political and legal landscape of Aotearoa New Zealand. From the collection of this data, we have found that approximately 1% of political science lecturers are Maori, 1% of content taught can be classified as Maori politics and approximately 1% of publications in the New Zealand Political Science journal can be classified as kaupapa Maori politics. This 1-1-1 crisis provides a bleak picture of the existing arrangements in politics programs in Aotearoa New Zealand and must change
Keywords: Indigenous peoples--Education; Māori (New Zealand people)--Education; Māori (New Zealand people)--Politics and government; New Zealand; Political science--Politics and government; Research--Evaluation

Kia aiō ngā ngaru, kia hora te marino: smoothing the waters in natural resource management to mitigate risk and uncertainty - Awatere, Shaun; Hyslop, Jade; Harcourt, Nikki; Hikuroa, Dan; Blackett, Paula; Heron, Richard Le (AlterNative: An International Journal of Indigenous Peoples, 2023)
Aotearoa (New Zealand) is undertaking reforms in natural resource management, and there are promising signals that Indigenous perspectives will be included alongside science for decision-making. Any resource management system is underpinned by worldviews, from which values stem and then risk and uncertainty derive. Māori (the Indigenous peoples of New Zealand) and Eurocentric notions of risk and uncertainty are fundamentally different because knowledge holders have different worldviews. Eurocentric concepts of risk and uncertainty continue to frame policy, making it challenging for Māori knowledge to shape policy that is relevant for decision-making in Aotearoa. We explore Māori perspectives of risk and uncertainty and literature, identifying common attributes across natural resource management frameworks, and identify issues of risk and uncertainty from the perspective of Māori experts. We conclude that a Māori approach to enhancing natural resources is more aligned to current environmental policy compared with standard approaches for risk assessment and reducing uncertainty.

The predictors of Māori electoral roll choice and knowledge: rangatahi Māori voter enrolment in a representative New Zealand youth survey - Greaves, Lara M.; Hayward, Janine; Barnett, Daniel; Crengle, Sue; Clark, Terryann C. (Kōtuitui: New Zealand Journal of Social Sciences Online, 2023)
Every five years and when initially enrolling to vote, Māori have the choice between the Māori roll or the general roll. Research has explored the predictors of roll choice for older adults, but this paper presents the first exploration of roll choice for rangatahi Māori (Māori youth; aged 13–18), and the predictors of rangatahi not understanding the difference between rolls. We draw on Māori data (n = 1528) from Youth19 which surveyed students from a random sample of schools from Tai Tokerau, Tāmaki Makaurau, and Waikato. We find those Māori who also identify as Pākehā (New Zealand European) are less likely to opt for the Māori roll, but those who know their Iwi, are comfortable in Māori social surroundings, feel a spiritual connection to land and the presence of their ancestors in their lives, or feel the drive to be respected as Indigenous, are more likely to choose the Māori roll. Older rangatahi are more likely to say they understand the question, as are those with study plans post-secondary school, and who say they are comfortable in Māori social settings. These results contribute to a body of knowledge valuable for those seeking to increase voter enrolment and enrolment on the Māori roll.Glossary of Māori words: Hapū: kinship group, generally smaller than Iwi; sometimes translated to sub-tribe; hui: meeting; Iwi: broader tribal unit or grouping; nation; kaitiaki: guardian, steward, trustee; kanohi-ki-te-kanohi: face to face/in person; kapa haka: Māori performing arts; traditional performance; Kura Kaupapa Māori: Māori language/Māori medium schools; mana whenua: Māori group(s) who have authority, power, or rights over a certain area of land; marae: meeting house and the area surrounding it; mātauranga Māori: Māori ways of knowing/knowledge; Pākehā: New Zealanders of European descent; rangatahi: youth; rohe: area, region; tangata whenua: Indigenous peoples of Aotearoa New Zealand; people(s) of the land; te reo Māori: the Māori language; te Tiriti o Waitangi: the Māori language version of the Treaty of Waitangi; tīpuna/tupuna: ancestors; waka ama: canoe sport; wānanga: meetings for discussion, deliberation, forums; whanau: family, extended family, or family-like group; whanaungatanga relationship, kinship, sense of family-like connections between people.
Keywords: māori roll; political participation; rangatahi; tūpuna; voter enrolment; voting

Who are the Māori “in-between”? Indigenous diversity and inequity across descent, ethnicity and Iwi knowledge - Greaves, Lara M.; Lindsay Latimer, Cinnamon; Li, Eileen; Hamley, Logan; Renfrew, Larissa; Sporle, Andrew; Milne, Barry (Ethnic and Racial Studies, 2023)
Policies increasingly reinforce the self-determination of Indigenous peoples, but issues remain around group definitions. Colonization has led to (de)identification with Māori (New Zealand's Indigenous peoples) identity markers. We explore differences between Māori on combinations of descent, ethnicity and Iwi (extended kinship group) knowledge in the 2013 Census, and self-reported discrimination. There were six groups within the Māori descent population: two did not know their Iwi – some identified solely as Māori ethnicity (2.8 per cent) – or Māori plus another ethnicity(-ies; 6.8 per cent); two did not identify as Māori ethnicity: more named their Iwi (7.2 per cent), than not (6.9 per cent); the largest groups knew their Iwi and identified as Māori ethnicity, either solely (30.8 per cent), or alongside another ethnicity(-ies; 34.3 per cent). We found a pattern of differences across demographics and discrimination, highlighting the complexity of Māori identity and the need to account for differences within Indigenous groups.
Keywords: crown policy; discrimination; ethnic identity; identity; whakapapa